Mechanism of CRP-mediated cya suppression in Escherichia coli. - Harman, J G (1983)
Escherichia coli strain NCR30 contains a cya lesion and a second-site cya suppressor mutation that lies in the crp gene. NCR30 shows a pleiotropic phenotypic reversion to the wild-type state in expressing many operons that require the cyclic AMP (cAMP)-cAMP receptor protein (CRP) complex for positive control. In vivo beta-galactosidase synthesis in NCR30 was sensitive to glucose-mediated repression, which was relieved not only by cAMP but also by cyclic GMP and cyclic CMP. The CRP isolated from NCR30 differed from the protein isolated from wild-type E. coli in many respects. The mutant protein bound cAMP with four to five times greater affinity than wild-type CRP. Protease digestion studies indicated that native NCR30 CRP exists in the cAMP-CRP complex-like conformation. The protein conferred a degree of cAMP independence on the in vitro synthesis of beta-galactosidase. In addition, the inherent positive control activity of the mutant protein in vitro was enhanced by those nucleotides that stimulate in vivo beta-galactosidase synthesis in NCR30. The results of this study supported the conclusion that the crp allele of NCR30 codes for a protein having altered effector specificity yet capable of promoting positive control over catabolite-sensitive operons in the absence of an effector molecule.